Inhibition of Thrombin-induced Neuronal Cell Death by Recombinant Thrombomodulin and E5510, a Synthetic Thrombin Receptor Signaling Inhibitor - Sarker, Krishna Pada; Abeyama, Kazuhiro; Nishi, Jun-ichiro; Nakata, Masanori; Tokioka, Takeshi; Nakajima, Toshihiro; Kitajima, Isao; Maruyama, Ikuro (Thrombosis and Haemostasis, 1999)
Thrombin, a serine protease generated by the activation of the blood coagulation cascade following vessel injury, converts fibrinogen to fibrin, activates platelets and several coagulation factors, and plays a pivotal role in thrombosis and haemostasis. Thrombin acts as a mitogen and apoptosis inducer in a dose-dependent fashion. We have previously shown that thrombin caused proliferation of vascular smooth muscle cells (VSMCs). Here, we show that a low concentration of thrombin caused proliferation of mouse neuroblastoma (Neuro-2a) and human neuroblastoma (NB-1) cells, while higher concentrations affected cell viability in a time-dependent manner. Similar effects were observed when thrombin receptor agonist peptide (SFLLRNPNDKYEPF, TRAP) was applied. The dying cells showed nuclear condensation and fragmentation, suggesting that cell death occurred by apoptosis. The extent to which thrombin induced cell death was significantly attenuated by recombinant thrombomodulin (rTM), or by a minimum functional domain of TM, termed E456. Furthermore, a synthetic compound that inhibits signaling from the thrombin receptor, 4-cyano-5,5-bis (4-methoxyphenyl)-4-pentanoic acid (E5510), and the antioxidant N-acetyl L-cysteine (NAC), efficiently prevented thrombin-induced Neuro-2a cell death. Thus, thrombin inhibitors and antioxidant appear to neutralize thrombin toxicity.